Maritime power and the law of the sea expeditionary operations in world politics - Kraska, James (New York ; Oxford : Oxford University Press, 2011)
Here, Commander James Kraska analyzes the evolving rules governing freedom of the seas and their impact on expeditionary operations in the littoral, near-shore coastal zone.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Economic zones (Law of the sea); Law of the sea; Territorial waters